Perception Of Benefits And Convenience In The Interest Of Use E-Money For Shopeepay Users In Wajo Regency - Yusi Irensi Seppa; Siti Syarifah Wafiqah Wardah (Public Resource Innovation Management and Excellence, 2025)
The increasing phenomenon of digital wallet use today indicates that people in this case have accepted digital payment applications to support daily transaction activities. This study aims to find out how the perception of benefits and convenience in the interest in using E-Money in Shopeepay users in Wajo Regency is perceived. The research approach used is a qualitative approach with a descriptive type of research. This research was conducted on Shopeepay users in Wajo Regency. Data collection procedures with observation, interviews and documentation. The data analysis used is the data collection technique used, namely data reduction, data presentation and conclusion drawn. From the results of the study, it was found that the perception of benefits and convenience makes users continue to be interested in using shopeepay e-money, especially in Wajo district. Shopeepay is an electronic money service that functions as a payment method and to store change funds offered by one of the largest marketplaces in Indonesia, namely Shopee. The perception of benefits is something that is always paid attention to by the public, with very helpful benefits, of course, people are interested in using products. The perception of ease of use is a consideration for the public in using electronic money services. The novelty of this research is that there is a novelty in the technological aspect, the aspect of consumer behavior and the economic aspect in the region. Keywords : Perception of Benefits, Convenience, Interest, E-Money, Shopeepay